Continuous hydrothermal synthesis of extensive 2D sodium titanate (Na2Ti3O7) nano-sheets. - Zhang, Z; Goodall, J; Brown, S; Karlsson, L; Clark, R; Hutchison, J; Rehman, I; Darr, J (2010)
A novel and rapid and continuous hydrothermal route to the synthesis of extensive ultra-thin 2D sodium titanate (Na(2)Ti(3)O(7)) nano-sheets using a superheated water flow at 450 degrees C and 24.1 MPa as a crystallizing medium is described. High resolution electron microscopy of the sheets revealed that they were a few layers thick and largely uncurled, highly crystalline despite their very short time under hydrothermal flow conditions. The sodium titanate sheets possessed excellent photocatalytic activity for decolourisation of methylene blue dye.